O que faz o medo de aprender na zona de desenvolvimento proximal? - Marta Santos; Marianne Lacomblez (Universidade do Porto, 2007)
This article presents a reflection on a learning situation in a training course for fishermen.After briefly presenting some of Vygostki´s concepts, we will show how, in some situations, in order to achieve effective learning we need to know not only how to identify the "true" concepts and to know the "zone" in which we are intervening (to allow cognitive and motivational development), but also what happens in the confrontation of this learning with the real. In the confrontation with "real life", the fear of losing the detained knowledge (that proves to be effective, "in spite of everything"), can be a variable that we should not neglect with regard to training. On the contrary, that variable should be debated in order to prevent the new knowledge from assuming an absolute statute, and becoming a mere imposition.